2011
DOI: 10.5402/2011/791319
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Delivery by Caesarean Section in Cameroon (2003-2004): A Regional Hospital Report

Abstract: We conducted this retrospective case-control study to identify possible risk factors of delivery through caesarean section in the Far North Region of Cameroon. Data was collected retrospectively from delivery room registers at the Provincial Hospital, Maroua, Cameroon from 01/01/2003 to 31/12/2004. The overall 125 eligible caesarean deliveries were compared with 244 women who delivered vaginally during the study period. The odds ratio as well as the 95% confidence interval was used to measure the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
14
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 10 publications
9
14
3
2
Order By: Relevance
“…Majority (72.3%) of mothers gestational age at labor was less than 38 weeks, but in study done in Oman the majority of the mothers gestational age is above 38 weeks [14]. in this study, maternal age is significantly associated with cesarean section in line with other different studies [14,15]. Being undergone cesarean section more likely increase as age of mothers increase.…”
Section: Discussionsupporting
confidence: 85%
“…Majority (72.3%) of mothers gestational age at labor was less than 38 weeks, but in study done in Oman the majority of the mothers gestational age is above 38 weeks [14]. in this study, maternal age is significantly associated with cesarean section in line with other different studies [14,15]. Being undergone cesarean section more likely increase as age of mothers increase.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of HBW, using the traditional cut-off value in our study (9.5%), was higher than that obtained by Abena Obama et al 9 (6.0%) and Tebeu et al 24 (4.3%) in 1995 and 2005, respectively, in Cameroon, suggesting that HBW is becoming more prevalent over time.…”
Section: Discussioncontrasting
confidence: 85%
“…Comparable results have been reported from younger maternal ages in Sudan and UAE [19][20]. Accordingly, higher incidences of C-section were reported among teenage wives of less than 17 years old [21]. In agreement with previous studies carried out in some developing countries, the teenage wives reported with higher prevalence rate of C-section exposure during this survey were mostly primiparous mothers [22].…”
Section: Discussionsupporting
confidence: 79%